2020
DOI: 10.24259/jhm.v12i1.9675
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Biomassa Dan Karbon Tersimpan Tegakan di Ruang Terbuka Hijau Kota Polewali, Sulawesi Barat

Abstract: Global warming is one of the major environmental issues of this century. Carbon dioxide (CO2) emissions are the main cause of global warming. Green open space (RTH) such as urban parks, urban forests and green lines play an important role in mitigating global warming and climate change in urban areas because it is able to reduce CO2 from the atmosphere. This study aims to determine the potential of biomass and carbon stored in the Green Open Green Space of Polewali, West Sulawesi. Data collection for stored bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Biomass and carbon stocks are determined by stand composition, age, circumference, and soil factors within the study area. Irundu et al [25] highlighted that carbon storage isn't influenced by a single parameter but by multiple factors like tree size, species diversity, and individual density. Dharmawan [26] suggested that the diameter class impacts stored biomass and carbon, where larger tree diameters absorb more carbon.…”
Section: Biomass and Carbon Stockmentioning
confidence: 99%
“…Biomass and carbon stocks are determined by stand composition, age, circumference, and soil factors within the study area. Irundu et al [25] highlighted that carbon storage isn't influenced by a single parameter but by multiple factors like tree size, species diversity, and individual density. Dharmawan [26] suggested that the diameter class impacts stored biomass and carbon, where larger tree diameters absorb more carbon.…”
Section: Biomass and Carbon Stockmentioning
confidence: 99%
“…Another thing that affects the value of carbon stocks is the value of tree biomass. According to Irundu et al (2020) and Indrajaya (2017), tree biomass can be determined by tree diameter, tree species diversity, number of individual trees, and tree density.…”
Section: Carbon Stock In Tree Biomassmentioning
confidence: 99%
“…This condition causes an increase in the ability of trees to store carbon from nature (Mustikaningrum, 2023). According to Komul et al (2016) and Sribianti et al (2022), trees have a large trunk diameter. This is because the results of the photosynthesis process are stored in the stem, causing the stem diameter to increase.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini menjadi bagian dari tanggung jawab perusahaan untuk menjalankan kebijakan pemerintah dalam peningkatan kesejahteraan Lansia yang diatur dalam Peraturan Pemerintah (PP) No. 43 Sukowati Field membentuk suatu program terkait perlindungan lingkungan berbasis pemberdayaan masyarakat yang mana akan berimbas pada meningkatnya kualitas kesehatan hidup warga yaitu penyediaan lahan TOSGA (Tanaman Obat dan Sayur Keluarga) yang berfungsi sebagai wadah masyarakat untuk lebih mengenal tanaman yang berkhasiat sebagai obat serta menambah taraf pelestarian lingkungan di sekitar wilayah desa Binaan Perusahaan (Irundu et al, 2020).…”
Section: Pertamina Peduli Lansia Bersinergi Produktif Dan Bahagia (Pe...unclassified